Dissection of the radical reactions linked to fetal hemoglobin reveals enhanced pseudoperoxidase activity - Ratanasopa, Khuanpiroon; Strader, Michael Brad; Alayash, Abdu I.; Bulow, Leif (Frontiers in Physiology, 2015)
In the presence of excess hydrogen peroxide (H2O2), ferrous (Fe+2) human hemoglobin (Hb) (α2β2) undergoes a rapid conversion to a higher oxidation ferryl state (Fe+4) which rapidly autoreduces back to the ferric form (Fe+3) as H2O2 is consumed in the reaction. In the presence of additional H2O2 the ferric state can form both ferryl Hb and an associated protein radical in a pseudoperoxidative cycle that results in the loss of radicals and heme degradation. We examined whether adult HbA exhibits a different pseudoenzymatic activity than fetal Hb (α2γ2) due to the switch of γ to β subunits. Rapid mixing of the ferric forms of both proteins with excess H2O2 resulted in biphasic kinetic time courses that can be assigned to γ/β and α respectively. Although there was a 1.5 fold increase in the fast reacting γ /β subunits the slower reacting phases (attributed to α subunits of both proteins) were essentially the same. However, the rate constant for the auto-reduction of ferryl back to ferric for both proteins was found to be 76% higher for HbF than HbA and in the presence of the mild reducing agent, ascorbate there was a 3 -fold higher reduction rate in ferryl HbF as opposed to ferryl HbA. Using quantitative mass spectrometry in the presence of H2O2 we found oxidized γ/β Cys93, to be more abundantly present in HbA than HbF, whereas higher levels of nitrated β Tyr35 containing peptides were found in HbA samples treated with nitrite. The extraordinary stability of HbF reported here may explain the evolutionary advantage this protein may confer onto co-inherited hemoglobinopathies and can also be utilized in the engineering of oxidatively stable Hb-based oxygen carriers.